STEM focused extracurricular programs: who's in them and do they change STEM identity and motivation?. Issue 4 (1st October 2020) - Stringer, Katie; Mace, Kevi; Clark, Tedra; Donahue, Tara
ABSTRACT: Background : Middle school students elected to participate in science, technology, engineering, and math (STEM) extracurricular programs (EPs). Researchers examined and compared science motivation, STEM career identity, and STEM college confidence among participants and non-participants. Purpose : The purpose of the study was to investigate differences in STEM EP participants and non-participants in their STEM motivation and identity at the beginning of participation, at the end of participation, and changes over time. Programme description : The STEM EPs in which students participated were Girls in STEM, Science Olympiad, and Math Counts. Girls in STEM focuses on exposing girls to STEM experiences and career. Science Olympiad complements classroom science through school-wide events, Science Fun Days or Science Fun Nights, and members have the option of competing in a tournament. Math Counts is a competitive mathematics program where students participate in spelling-bee-style competitions after receiving targeted math coaching. Sample : This study was conducted at a STEM-focused middle school (grades 6–8); 733 students (59% female) completed both the fall and spring surveys, with 71 students in STEM EPs (41% female) taking both surveys. Design and methods: Students completed surveys aimed at assessing science motivation, STEM career identity, and STEM college confidence in the fall and spring. Researchers analyzed data using logistic regression and linear mixed modeling. Results : Girls who participate in STEM EPs have a stronger STEM career identity and greater science motivation than non-participant girls. STEM EP participation is associated with greater spring science motivation and STEM career identity and less decline in STEM motivation and career identity from fall to spring. Conclusions : There are gender differences in characteristics of students who participate in STEM EPs. STEM EPs have the power to reduce declines in STEM career identity and science motivation typically experienced in middle school.